ANALYSIS OF RETURN VISITS TO YOGYAKARTA PALACE HERITAGE TOURISM DURING THE COVID-19 ENDEMIC - Novanda, Friendy; Permana Saputra, Asep Rokhyadi; Santosa, Awan; Widarto (Universitas Nusantara PGRI Kediri, 2023)
One of the tourist destinations that is used as an icon in the Special Region of Yogyakarta is the Palace and other cultural heritage. Keraton which is the face of the Special Region of Yogyakarta is the official residence of the Sultan of Yogyakarta which is open to the public. The uniqueness of the shape of the building and the simplicity of the way of life in the Palace are the main attractions of tourists who are visiting the Special Region of Yogyakarta. The community around the palace uses palace tourism as a source of income. Most of the area is managed by Abdi Dalem keraton. In addition to being a source of income, the surrounding community uses it as an object of introduction to Yogyakarta culture to visitors. The purpose of this study is to analyze the influence of environmental problems on the return visit of Yogyakarta palace. To analyze the influence of palace performances on the return visit of Yogyakarta palace. To analyze the effect of health protocols on the return visit to the Yogyakarta palace, the Research Method uses multiple linear regression. Environmental issues did not have a significant effect on the return visit of the Yogyakarta palace. The performance of the palace has a significant influence on the return visit of the Yogyakarta palace. Health Protocols have a significant effect on the return visit of the Yogyakarta palace.